Ad hoc transient communities: towards fostering knowledge sharing in learning networks. (10th July 2008) - Berlanga, Adriana J.; Sloep, Peter B.; Kester, Liesbeth; Brouns, Francis; Rosmalen, Peter; Koper, Rob
To enhance users' social embedding within learning networks, we propose to establish ad hoc transient communities. These communities serve a particular goal, exist for a limited period of time and operate according to specific social exchange policies that foster knowledge sharing. This paper explores the theoretical underpinnings of such communities. To this end, it identifies five theories that explain how group interaction affects community behaviour and argues that these can shed light on the expected behaviour of ad hoc transient communities. The paper also examines three conditions which community policies should adhere to in order to foster knowledge sharing and it suggests that ad hoc transient communities should be designed accordingly. Finally, it analyses how ad hoc transient communities can be implemented in an Information Technology (IT) platform which is currently under development, the TenCompetence Personal Competence Manager (PCM), and discusses the current practices in communities outside the learning arena. Finally, the paper explores the avenues for further work.